2021
DOI: 10.1021/acs.orglett.1c01673
|View full text |Cite
|
Sign up to set email alerts
|

Ad Hoc Adjustment of Photoredox Properties by the Late-Stage Diversification of Acridinium Photocatalysts

Abstract: The steadily growing interest in substituting precious-metal photoredox catalysts with organic surrogates is vibrantly sustained by emerging methodologies to vary their photochemical behavior. Herein, we report an ad hoc approach for the preparation of acridinium salts with a particularly broad range of photoredox properties. The method involves an aryne–imine–aryne coupling to a linchpin tetrafluoro acridinium salt for a late-stage diversification by nucleophilic aromatic substitution reactions to form diamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Intriguingly, we observed that upon oxidation of ( R )‐ 2 l with DDQ, the dichloro‐substituted acridinium salt ( R a )‐ 3 l (97 : 3 e.r.) was capable of undergoing nucleophilic aromatic substitutions with appropriate nucleophiles [12h] . A late‐stage diversification of ( R a )‐ 3 l was thus successfully carried out, providing the amino‐functionalized, atropisomeric acridiniums ( R a )‐ 4 a and ( R a )‐ 4 b with an e.r.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, we observed that upon oxidation of ( R )‐ 2 l with DDQ, the dichloro‐substituted acridinium salt ( R a )‐ 3 l (97 : 3 e.r.) was capable of undergoing nucleophilic aromatic substitutions with appropriate nucleophiles [12h] . A late‐stage diversification of ( R a )‐ 3 l was thus successfully carried out, providing the amino‐functionalized, atropisomeric acridiniums ( R a )‐ 4 a and ( R a )‐ 4 b with an e.r.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group investigated an approach towards acridinium photocatalysts that exploited an ad hoc, late-stage derivatization of the tetrafluorinated acridinium derivative via nucleophilic aromatic substitution reactions (Scheme 1c ). 19 The required tetrafluorinated acridinium salt was prepared in two steps by the aryne–imine–aryne coupling reaction 20 affording the corresponding acridane, which was subsequently oxidized with nitrosonium tetrafluoroborate. To expand the scope of organic photocatalysts with a broad range of photophysical properties, 16 we questioned whether our synthetic route towards the late-stage diversification substrate could also be applied for the preparation of other novel acridinium photocatalysts.…”
Section: Table 1 Scope and Photophysical Properties Of ...mentioning
confidence: 99%
“…Having all starting materials in hand, we centered our attention on the exploration of the reaction scope (Table 1 ). As the preparation of acridinium salt 1aa was earlier reported by our group, 19 we tested these established conditions for the synthesis of other tetrafluorinated acridinium salts (Figure 1 ). Gratifyingly, the reactions between difluorinated aryne precursor 2a and imines 3b and 3c afforded the desired acridanes that were successfully oxidized with nitrosonium tetrafluoroborate yielding products 1ab and 1ac , albeit with lower yields than for compound 1aa .…”
Section: Table 1 Scope and Photophysical Properties Of ...mentioning
confidence: 99%
“…[4][5][6] In recent studies, we investigated a short two-step route towards diverse acridinium salts involving the aryne-imine-aryne coupling reaction [7] followed by the subsequent oxidation of the acridane intermediate (Scheme 1,a). [8,9] Herein, we now disclose the utilization of this methodology for larger polycyclic aryne substrates. The unique reactivity of arynes containing an extended π-system under typical aryne-imine-aryne coupling conditions thereby lead to the notable formation of the tetrabenzo[a,c,i,k]phenanthridin-17ium system (Scheme 1,b).…”
Section: Introductionmentioning
confidence: 99%
“…Acridinium salts are particularly useful scaffolds and have emerged as an efficient and sustainable class of cationic organic photocatalysts [4–6] . In recent studies, we investigated a short two‐step route towards diverse acridinium salts involving the aryne‐imine‐aryne coupling reaction [7] followed by the subsequent oxidation of the acridane intermediate ( Scheme 1 ,a ) [8,9] …”
Section: Introductionmentioning
confidence: 99%